2016
DOI: 10.1017/s1355617716000886
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Reduces Face Processing Time but Leaves Recognition Accuracy and Eye-Gaze Unaffected

Abstract: These findings suggest that OXT-induced enhanced facial emotion recognition is not necessarily mediated by an increase in attention to the eye-region of faces, as previously assumed. We discuss several methodological issues which may explain discrepant findings and suggest the effect of OXT on visual attention may differ depending on task requirements. (JINS, 2017, 23, 23-33).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
1
36
2
Order By: Relevance
“…Specifically, the participants' information from their self-perspectives still influenced the process of adopting the views of the avatars, lending more accuracy when judging from one's own perspective than from others' perspectives. The results agree with similar results and explanations provided by other studies; i.e., Hubble et al ( 2017 ) and Di Simplicio et al ( 2009 ), who also reported a lack of effects of OXT on the accuracy in their tasks. This may indicate that the weakening effect of OXT on the egocentric bias in perspective taking may also have limitations, which indicates that self-centeredness is, to a great degree, still a default choice when accurately inferring other people's mental states.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the participants' information from their self-perspectives still influenced the process of adopting the views of the avatars, lending more accuracy when judging from one's own perspective than from others' perspectives. The results agree with similar results and explanations provided by other studies; i.e., Hubble et al ( 2017 ) and Di Simplicio et al ( 2009 ), who also reported a lack of effects of OXT on the accuracy in their tasks. This may indicate that the weakening effect of OXT on the egocentric bias in perspective taking may also have limitations, which indicates that self-centeredness is, to a great degree, still a default choice when accurately inferring other people's mental states.…”
Section: Discussionsupporting
confidence: 93%
“…During the waiting period, OXYTOCIN, EMPATHY AND EYE-GAZE participants completed a set of measures asking for demographics and food and caffeine intake. At the end of the waiting period they completed a 15-minute face processing task (see Hubble et al, 2016), which was followed by the empathy task that started minutes after OXT administration and lasted approximately minutes. Each video clip was followed immediately by the empathy questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, within the ASD literature there is evidence that improved facial emotion recognition is due, in part, to participants spending more time looking at the eye area of faces (e.g., Andari et al, 2010). Nevertheless, evidence from healthy participants to support this line of argument is mixed, with one study suggesting that OXT selectively enhances gaze to the eyes (Auyeung et al 2015), another showing that OXT results in increased gaze to the eye areas for positive faces but decreased gaze to the eyes for negative faces (Domes, Steiner, Porges & Heinrichs, 2013), and others suggesting that improvements in facial emotion recognition are unaffected by eye-gaze (Hubble et al, 2016;Lischke et al, 2012;), but instead are related to pupil dilation (Prehn et al, 2013).…”
Section: Oxytocin Empathy and Eye-gazementioning
confidence: 99%
“…Five studies investigated the effects of a single dose of intranasal oxytocin on attention towards regions of interest (ROIs) in threatening images using eye tracking (Table 1). Three of the studies defined the ROIs as the eye and mouth region of angry and disgusted faces (Bertsch et al, 2013;Domes et al, 2013;Hubble et al, 2017;Lischke et al, 2012a). One study investigated fixation towards predefined regions of interest in threatening scenes taken from the international picture affective system (Lischke et al, 2012b).…”
Section: Attentional Responsesmentioning
confidence: 99%